Photothermal Lens Spectrometry Measurements in Highly Turbid Media. Issue 9 (September 2013) - Marcano, Aristides; Basaldua, Isaac; Villette, Aaron; Edziah, Raymond; Liu, Jinjie; Ziane, Omar; Melikechi, Noureddine
We measured the photothermal lens signal in samples exhibiting high turbidity using a pump-probe scheme. We show that the photothermal lens signal properties remain nearly unchanged up to values of turbidity of 6 cm −1 despite the signal reduction due to the decrease of excitation power associated to turbidity losses. The signal starts decreasing abruptly for values of turbidity larger than 6 cm −1 . Multiple light scattering yields a reduction of the temperature gradients' which results in a decrease of the effective signal. However, the signal-to-noise ratio remains above 50 for turbidity values of 9 cm −1, which corresponds to a reduction of light transmission by more than four orders of magnitude. We report on the detection of the photothermal lens signal through a 2 mm layer of organic tissue with a signal-to-noise ratio of about 500. This technique appears promising for imaging applications in organic samples, which usually exhibit high turbidity for visible and near-infrared light.